HUBUNGAN KONSEP DIRI DENGAN PERENCANAAN KARIR MAHASISWA BIMBINGAN KONSELING ISLAM ANGKATAN 20 UIN SUSKA RIAU - Rahmad; Ifdil; Afdal; Marjohan (Yayasan Amanah Nur Aman, 2024)
The increasing number of college graduates each year causes tighter competition in the world of work. This study aims to determine the relationship between self-concept and career planning of Islamic Guidance Counseling Students of Class 20 K UIN Suska Riau.The population in this study was 211 students. For the sample using purposive sampling method totaling 13 people, while to determine the relationship between the basic variable (x) and the dependent variable (y), the Product Moment Correlation test method was used, obtained a correlation coefficient (r) of 0.947 based on the results of product moment correlation analysis p=0.000 (p<0.01) which means that there is a very significant positive relationship between self-concept and career planning. based on the amount of correlation value in the product moment interpretation table 0.800-1.000 shows a very strong correlation category.